Answers

2016-07-03T19:00:09+08:00
An=a1+(n-1)d -18=7+(n-1)-5 -18=7+(-5n+5) -18-7-5=-5n -30=-5n Divide each by -5. The answer is 6=n.
0
wrong
^Jane75, Jembhel's answer is the correct one.
Prove it.
Comment has been deleted
But for your benefit, I'll post my answer. But I give credit to Jembhel for posting the correct answer first.
  • Brainly User
2016-07-03T19:15:41+08:00
General formula:

 a_{n} = a₁ + (n-1) (d)

d = a₂ - a₁
d = 2 - 7
d = -5
a₁ = 7
an = -18
n = ?

Solution:
-18 = 7 + (n-1) (-5)
-18 = 7 -5n + 5
-18 = -5n + 12
5n = 12 + 18
5n/n = 30/5
n = 6

ANSWER:  -18 is the 6th term of the given sequence.
0